Conventional Type 1 Dendritic Cells (cDC1) in Human Kidney Diseases: Clinico-Pathological Correlations - Chen, Titi; Cao, Qi; Wang, Ruifeng; Zheng, Guoping; Azmi, Farhana; Wang, Jeffery; Lee, Vincent W.; Wang, Yuan Min; Yu, Hong; Patel, Manish; P’ng, Chow Heok; Alexander, Stephen I.; et al. (Frontiers in Immunology, 2021)
Background cDC1 is a subset of conventional DCs, whose most recognized function is cross-presentation to CD8+ T cells. We conducted this study to investigate the number and location of cDC1s in various human kidney diseases as well as their correlation with clinico-pathological features and CD8+ T cells. Methods We analyzed 135 kidney biopsies samples. Kidney diseases included: acute tubular necrosis (ATN), acute interstitial nephritis (AIN), proliferative glomerulonephritis (GN) (IgA nephropathy, lupus nephritis, pauci-immune GN, anti-GBM disease), non-proliferative GN (minimal change disease, membranous nephropathy) and diabetic nephropathy. Indirect immunofluorescence staining was used to quantify cDC1s, CD1c+ DCs, and CD8+ T cells. Results cDC1s were rarely present in normal kidneys. Their number increased significantly in ATN and proliferative GN, proportionally much more than CD1c+ DCs. cDC1s were mainly found in the interstitium, except in lupus nephritis, pauci-immune GN and anti-GBM disease, where they were prominent in glomeruli and peri-glomerular regions. The number of cDC1s correlated with disease severity in ATN, number of crescents in pauci-immune GN, interstitial fibrosis in IgA nephropathy and lupus nephritis, as well as prognosis in IgA nephropathy. The number of CD8+ T cells also increased significantly in these conditions and cDC1 number correlated with CD8+ T cell number in lupus nephritis and pauci-immune GN, with many of them closely co-localized. Conclusions cDC1 number correlated with various clinic-pathological features and prognosis reflecting a possible role in these conditions. Their association with CD8+ T cells suggests a combined mechanism in keeping with the results in animal models.